Relationship between hair and salivary cortisol and pregnancy in women undergoing IVF - Massey, Adam; Campbell, Bruce K.; Raine-Fenning, Nick; Pincott-Allen, Catherine; Perry, Jane; Vedhara, Kavita (Elsevier, 2016)
Evidence for an association between cortisol and clinical pregnancy in women undergoing In Vitro Fertilisation (IVF) is mixed with previous studies relying exclusively on short term measures of cortisol in blood, saliva, urine, and/or follicular fluid. Hair sampling allows analysis of systemic levels of cortisol over the preceding 3–6 months. The present study sought to explore the relationship between cortisol and clinical pregnancy outcome in women undergoing IVF utilising multiple indices of cortisol derived from both saliva and hair measured prior to commencing gonadotrophin treatment. A total of 135 women (mean age 34.5 SD +/−4.8) were recruited from an English fertility clinic (December 2012–April 2014) 60% of whom became pregnant (n = 81). Salivary cortisol data were obtained over two days: upon awakening, 30 min post awakening, and at 22:00. A subsample (n = 88) of the women providing salivary samples were approached consecutively to provide hair samples for the measurement of cortisol. Independent Logistic regression analyses revealed that salivary cortisol measures including cortisol awakening response (CAR) (p = 0.485), area under the curve with respect to ground (AUCg) (p = 0.527), area under the curve with respect to increase (AUCi) (p = 0.731) and diurnal slope (p = 0.889) did not predict clinical pregnancy. In contrast, hair cortisol concentrations significantly predicted clinical pregnancy (p = 0.017). Associations between hair cortisol and clinical pregnancy remained when controlling for accumulations of salivary cortisol (p = 0.034) accounting for 26.7% of the variance in pregnancy outcome. These findings provide preliminary evidence that longer term systemic cortisol may influence reproductive outcomes; and in turn suggests that interventions to reduce cortisol prior to commencing IVF could improve treatment outcomes.